2013
DOI: 10.1007/s00296-013-2866-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to accessing biologic treatment for rheumatoid arthritis in Greece: the unseen impact of the fiscal crisis—the Health Outcomes Patient Environment (HOPE) study

Abstract: The latest regulatory change in the distribution system of biologic disease-modifying, antirheumatic drugs limited their sale only through the designated pharmacies of the National Organization for Healthcare Services Provision (EOPYY) or the National Health System (NHS) hospitals, adding to the complexity of access to effective treatment for rheumatoid arthritis (RA) in Greece. The aim of this paper was to assess the barriers to access RA treatment, by recording patients', rheumatologists' and EOPYY pharmacis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 18 publications
5
38
1
1
Order By: Relevance
“…Findings from this study are in line with those of the HOPE I and II studies (8,9) for patients with In 2012, patients experiencing rheumatoid arthritis also cited difficulties in accessing medication, the long geographical distance from health services, the long waiting lists for appointment and the low availability of medicines from NHS hospitals as the main inhibitors for access to the treatment (8). Moreover, in 2014, the HOPE II study revealed that patients suffering from multiple sclerosis faced barriers such as problems in accessing medical and pharmaceutical treatment because of long distance from pharmacies and health services, the low availability of pharmaceutical medication and the financial burden of the out of pocket costs (9).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Findings from this study are in line with those of the HOPE I and II studies (8,9) for patients with In 2012, patients experiencing rheumatoid arthritis also cited difficulties in accessing medication, the long geographical distance from health services, the long waiting lists for appointment and the low availability of medicines from NHS hospitals as the main inhibitors for access to the treatment (8). Moreover, in 2014, the HOPE II study revealed that patients suffering from multiple sclerosis faced barriers such as problems in accessing medical and pharmaceutical treatment because of long distance from pharmacies and health services, the low availability of pharmaceutical medication and the financial burden of the out of pocket costs (9).…”
Section: Discussionsupporting
confidence: 94%
“…The first study (HOPE I) was conducted in 2012 and revealed that a large majority of patients with rheumatoid arthritis experiencing significant difficulties in accessing medication. Furthermore, the most common barriers to treatment was the geographical distance from physician's setting, the long waiting lists for appointment as well as the low availability of medicines from National Health Service (NHS) hospitals and the complicated prescription process (8). The second study (HOPE II) was carried out in 2014 and revealed that same barriers do also exist for patients suffering from multiple sclerosis (9).…”
Section: Introductionmentioning
confidence: 98%
“…7,[12][13][14][15] Yet, despite the improvement in the operation of the distribution system, problems still exist, with one in eight MS patients reporting barriers in accessing bDMDs. Similarly to the previous HOPE I study, 11 the distance from EOPYY pharmacies continued to present a major obstacle for patients, while other obstacles were related to the difficulties in obtaining the required medical diagnosis by an ESY/EOPYY physician, and to the reduced accessibility of patients to their treating physician. These barriers could be overcome through the development of an MS national registry which would standardize the distribution process (and home delivery) and assure comprehensive, and faster patient access to treatment.…”
Section: Discussionmentioning
confidence: 97%
“…This resulted in anxiety, confusion and discomfort for patients, who often had to travel long distances to ensure access to their medicines. As shown in the HOPE I study by Souliotis et al, 11 one in 2 patients with RA reported problems in accessing biologic DMARDs during 2012 through the new system, which they attributed to the long distance from EOPYY pharmacies, difficulties in accessing a prescribing a Treatment requiring or not short-term hospitalization. doctor and to the non-availability or difficulty of finding their medication at an ESY hospital or EOPYY pharmacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation